COMMUNITY EMPOWERMENT IN THE MANAGEMENT AND BUSINESS OPPORTUNITIES OF WASTE BANKS IN GRIYA PERMATA ASRI HOUSING SERANG CITY: PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN DAN PELUANG USAHA BANK SAMPAH DI PERUMAHAN GRIYA PERMATA ASRI KOTA SERANG - Mohamad Husni; Riyanthi Idayu; Angga Anggriawan; Dedi Sutendi; Aski Atsriya Pramudiaspuri; Selda Setianti (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Departing from concern for waste, which in its management faces various obstacles, generally in the city of Serang and especially in the Griya Permata Asri housing complex, all of this is a result of the increasing number of residents living in Griya Permata Asri, through community service we strive to make waste more valuable. higher economic value in terms of management, therefore we provide an alternative in waste management by establishing a waste bank which in its management can improve the economy of residents in Griya Permata Asri. The method and approach used in this community service is the Short Learning by Doing method, namely by using the Discussion and Practice method in its implementation, the results we hope for in this Community Service Program are: 1. Residents of Griya Permata Asri are increasingly aware of the dangers of waste. 2. Residents of Griya Permata Asri know how to sort organic and non-organic waste and know which waste can have economic value if it is recycled. 3. Residents of Griya Permata Asri know and understand the mechanism for establishing a waste bank and the procedures for its management. The outcome of this Community Service program is that residents are expected to be able to maintain the sustainability of the waste bank operations at Griya Permata Asri Housing